Time in the experience of agency and emotion in English language learning in rural Vietnam. Issue 3 (2nd September 2017) - White, Cynthia; Pham, Cuong
ABSTRACT: While time and context have been found to have both synergistic and cumulative effects on language learners' cognitive and socio-affective development, time itself remains under-conceptualised in those processes. Drawing on the Bakhtinian construct of chronotope Bakhtin [(1981). The Dialogic Imagination: Four Essays . Translated by Caryl Emerson and Michael Holquist. Austin: University of Texas Press], and Blommaert's [(2015). "Chronotopes, Scales, and Complexity in the Study of Language in Society." Annual Review of Anthropology 44: 105–116. doi:10.1146/annurev-anthro-102214-014035 ] emphasis on its essential connection to historical and momentary agency, we analyse narrative accounts of three high school students learning English in rural Vietnam from a dialogical perspective. Specifically, we identify how different chronotopes are implied and expressed involving a range of settings, social actors, artefacts, actions and timescales as the students author themselves as English language learners. Importantly, we examine how these chronotopes function as frames in which time, settings, agency and emotion are entwined, assuming different significance and generating meanings which can merge, collide and conflict with other chronotopes. We reveal how chronotopes are implicated in the ways in which learners construct their agency at specific moments within particular settings, and argue that emotion is a central component in those processes. To conclude, we suggest that the construct of chronotope is a valuable tool for developing more complex, fine-grained understandings of how students construct meaning within and across multiple time-space configurations as they author their lifeworlds.